A new immunodeficient Duchenne muscular dystrophy rat model to evaluate engraftment after human cell transplantation - Sato, Masae; Goto, Megumi; Yamanouchi, Keitaro; Sakurai, Hidetoshi (Frontiers in Physiology, 2023)
Duchenne muscular dystrophy (DMD) is an X-linked fatal muscular disease, affecting one in 3,500 live male births worldwide. Currently, there is no cure for this disease, except for steroid-based treatment to attenuate disease progression. Cell transplantation therapy is a promising therapeutic approach, however, there is a lack of appropriate animal models to conduct large-scale preclinical studies using human cells, including biochemical and functional tests. Here, we established an immunodeficient DMD rat model and performed exhaustive pathological analysis and transplantation efficiency evaluation to assess its suitability to study DMD. Our DMD rat model exhibited histopathological characteristics similar to those observed in human patients with DMD. Human myoblasts demonstrated successful engraftment following transplantation into these rats. Therefore, this immunodeficient DMD rat model would be useful in preclinical studies to develop cellular transplantation therapies for DMD.